Sub-Saharan African Maize-Based Foods - Processing Practices, Challenges and Opportunities. Issue 7 (3rd October 2019) - Ekpa, Onu; Palacios-Rojas, Natalia; Kruseman, Gideon; Fogliano, Vincenzo; Linnemann, Anita R.
ABSTRACT: In vast swathes of Sub-Saharan Africa, maize is the staple food with consumption of up to 450 g/person/day. Additionally, maize is used as a weaning food for infants as well as for special ceremonies, caring for the sick, aged and pregnant women. Malnutrition persists in regions with heavy maize consumption, partly due to compositional maize characteristics, nutrient loss during processing and consumer preferences. This paper reviews the traditional uses and processing of maize, opportunities and necessary improvements to ensure (micro)nutrient security. Better use of maize can enhance its contribution to meeting the dietary needs and livelihood of Africa's growing populace.